Crystal chemistry of natural layered double hydroxides: 4. Crystal structures and evolution of structural complexity of quintinite polytypes from the Kovdor alkaline-ultrabasic massif, Kola peninsula, Russia. (28th February 2018) - Zhitova, Elena S.; Krivovichev, Sergey V.; Yakovenchuk, Viktor N.; Ivanyuk, Gregory Yu.; Pakhomovsky, Yakov A.; Mikhailova, Julia A.
Abstract: Two quintinite polytypes, 3 R and 2 T, which are new for the Kovdor alkaline-ultrabasic complex, have been structurally characterized. The crystal structure of quintinite-2 T was solved by direct methods and refined to R 1 = 0.048 on the basis of 330 unique reflections. The structure is trigonal, P $\bar 3$ c 1, a = 5.2720(6), c = 15.113(3) Å and V = 363.76(8) Å 3 . The crystal structure consists of [Mg2 Al(OH)6 ] + brucite-type layers with an ordered distribution of Mg 2+ and Al 3+ cations according to the $\sqrt 3 $ × $\sqrt 3 $ superstructure with the layers stacked according to a hexagonal type. The complete layer stacking sequence can be described as …=Ab 1 C = Cb1 A =…. The crystal structure of quintinite-3 R was solved by direct methods and refined to R 1 = 0.022 on the basis of 140 unique reflections. It is trigonal, R $\bar 3$ m, a = 3.063(1), c = 22.674(9) Å and V = 184.2(1) Å 3 . The crystal structure is based upon double hydroxide layers [ M 2+, 3+ (OH)2 ] with disordered distribution of Mg, Al and Fe and with the layers stacked according to a rhombohedral type. The stacking sequence of layers can be expressed as …=АB = BC = CA =… The study of morphologically different quintinite generations grown on one another detected the following natural sequence of polytype formation: 2 H → 2 T → 1 M that can be attributed to a decrease of temperature during crystallization. According to the information-based approach to structural complexity, this sequence corresponds to the increasing structural information per atom ( I G ): 1.522 → 1.706 → 2.440 bits, respectively. As the I G value contributes negatively to the configurational entropy of crystalline solids, the evolution of polytypic modifications during crystallization corresponds to the decreasing configurational entropy. This is in agreement with the general principle that decreasing temperature corresponds to the appearance of more complex structures.